Dispositions: An Integrational Analysis. (May 2015) - Chung, Daihyun
Whereas the Humean accounts of causality in terms of contiguity, temporal priority, constant conjunction, and contingency face difficulties of one sort, the dispositional explanations of causality in terms of reciprocity, simultaneity, ubiquity, and holism seem to meet difficulties of another sort. But the difficulties which dispositionalism faces may be dissipated if one can appeal consistently to the logic of naturalism, rather than to the grammar of an implicit dualism, for example, as it is illustrated when G. Molnar tried to advance the analogy between the mental intentionality and the physical intentionality. The notion of integration is taken to allow a conceptual space for naturalism of one kind. It may be expressed in the thesis that there is integrationality in any entity like dispositions, such that the integrationality is a power to realize the embedded objective of it in the context where it interacts with all others. The thesis would help to see how dispositions can be intentional, how the notion of information may be read integrationally from any object, and how the notion of fitting plays a role in the metaphysics of integrationality.